1994
DOI: 10.1161/01.str.25.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion after thrombolytic therapy in ischemic stroke measured by single-photon emission computed tomography.

Abstract: Background and PurposeWe used Tc-hexamethylpropyleneamine oxime single-photon emission computed tomography (SPECT) to study cerebral perfusion in patients treated with streptokinase for acute ischemic stroke in an open and prospective study. Our primary aims were (1) to compare the extent of reperfusion between patients who had received thrombolytic therapy and a control group studied during the same period who were ineligible to receive such therapy and (2) to determine if, among all patients, reperfusion led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 25 publications
(12 reference statements)
4
59
0
Order By: Relevance
“…78 In addition, pericyte death in rigor results in a permanent decrease in blood flow in capillaries and damages neurons after stroke. [94][95][96] These mechanisms resemble FIR in improving capillary dilation and blood flow and may reflect the promotion of stroke recovery by FIR stimulation. In other words, FIR therapy may alleviate stroke by inhibiting pericyte death.…”
Section: Discussionmentioning
confidence: 95%
“…78 In addition, pericyte death in rigor results in a permanent decrease in blood flow in capillaries and damages neurons after stroke. [94][95][96] These mechanisms resemble FIR in improving capillary dilation and blood flow and may reflect the promotion of stroke recovery by FIR stimulation. In other words, FIR therapy may alleviate stroke by inhibiting pericyte death.…”
Section: Discussionmentioning
confidence: 95%
“…90 Recanalization and reperfusion status were fairly correlated in the other three patients, and one additional patient had undergone partial reperfusion despite unsuccessful recanalization. 90 In another study, which compared the efficacy of intravenous streptokinase against placebo, out of 10 patients with initial vessel occlusion, 4 had successful recanalizaton, yet impaired reperfusion. 91 Reperfusion and recanalization were correlated in the remaining eight patients; six attained successful recanalization and reperfusion, whereas the remaining two reached neither end point.…”
Section: Can We Improve the Stroke Outcome After Thrombolysis?mentioning
confidence: 77%
“…90,91 In one study, out of five patients with an initial perfusion defect on serial single photon emission CT together with an intracranial artery occlusion, one patient had no cerebral reperfusion despite partial recanalization of MCA with intraarterial streptokinase. 90 Recanalization and reperfusion status were fairly correlated in the other three patients, and one additional patient had undergone partial reperfusion despite unsuccessful recanalization. 90 In another study, which compared the efficacy of intravenous streptokinase against placebo, out of 10 patients with initial vessel occlusion, 4 had successful recanalizaton, yet impaired reperfusion.…”
Section: Can We Improve the Stroke Outcome After Thrombolysis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of patients included in this study is very small, the data are consistent with clinical response observed in our patients and with other studies of cerebral perfusion and thrombolysis in the literature. [3][4][5] One implication of our study is that clinical criteria alone without confirmatory measurement of cerebral perfusion is sufficient to establish that most patients who qualify for rtPA therapy on clinical grounds also have a significant cerebral ischemic lesion. The patient population in this SPECT study did not include those with brain stem infarcts but did include patients suspected of having either cortical or lacunar hemispheric strokes.…”
Section: Discussionmentioning
confidence: 87%